The Role of Labor Law in National Economic Development - Malau, Parningotan; Franky, Ramon; Situmorang, Sahala Tua; Wardani, Dian Wiris Woro (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
Labor law is a strategic instrument in regulating the relationship between workers and employers, as well as ensuring social justice in the workplace. Its aim is to create a balance of interests among all involved parties and to guarantee the protection of workers’ fundamental rights, such as the right to fair wages, humane working hours, social security, occupational safety and health, and the right to organize and engage in collective bargaining. The existence of this law is not only crucial for the protection of labor rights but also significantly contributes to economic stability and growth. This article aims to examine the extent to which labor law can create a fair, productive, and sustainable employment ecosystem in the context of national economic development. The method used is a juridical-normative and empirical approach through secondary data analysis and literature review. The findings show that the effective implementation of labor law can enhance productivity, reduce industrial conflict, and encourage investment through the creation of legal certainty. Therefore, labor regulatory reform and institutional strengthening are key prerequisites for sustainable economic development. In addition, labor law contributes to the creation of legal certainty and a conducive business climate. Labor regulation certainty is one of the key indicators in the Ease of Doing Business index. Legal reforms such as the Job Creation Law (UU Cipta Kerja) demonstrate efforts to align regulations with the needs of the business sector, although their effectiveness still needs to be tested in practical implementation.